Cost-Effectiveness Analysis in Reducing Nutrient Loading in Baltic and Black Seas: A Review - HALKOS, George E.; GALANI, Georgia K. (Journal of Environmental Management and Tourism; Vol 5 No 1 (2014): JEMT Volume V Issue 1(9) Summer 2014, 2016)
Eutrophication represents a global environmental pressure that necessitates international co-operation and the diffusion of information to avoid information asymmetries; the construction of an appropriate legislative framework; the development of monitoring technologies and scientific research to provide the evidence for policy intervention. The health condition of the Baltic and Black Seas has deteriorated over a long period due to increases in nutrient inputs from anthropogenic and non-anthropogenic sources. The current study aims at providing a review of the literature and defining the possible gaps concerning (1) the efforts toward a sustainable marine management in the Baltic and Black Seas; (2) the methodological issues in constructing a cost-effectiveness analysis and the uncertainties entailed in the cost-effectiveness studies, and (3) the available applications of cost-effectiveness studies conducted.
Keywords: eutrophication, cost-effectiveness analysis, abatement measures, nutrient loading, Baltic Sea, Black Sea